Consumer Awareness and Behavior toward the Risks of Harmful Ingredients in Skincare Products: A Thematic Analysis in the Digital Era - Haykal, Azzahrah Putri; Suhud, Usep; Rizan, Mohamad (Siber International Journal of Digital Business (SIJDB), 2025)
This study examines consumer awareness regarding the risks of hazardous ingredients in widely used skincare products in Indonesia. The research background highlights the high usage of skincare products, often without adequate understanding of their composition and potential dangers. The objective of this study is to analyze how consumers identify harmful ingredients, their experiences with unsafe products, and behavioral changes that follow. This research employs a qualitative method through thematic analysis of open-ended responses from skincare users. The results indicate that consumers are increasingly selective, prioritizing product legality and ingredient transparency, and utilizing social media, ingredient-checking applications, and professional consultations as sources of information. Moreover, negative experiences such as skin irritation and other side effects contribute to a more cautious and critical attitude toward product claims. The study concludes that education, transparent information, and consumer protection are key elements in fostering safe and responsible skincare consumption practices.